Standards for recanalisation of chronic venous outflow obstructions - Lichtenberg, Michael Klaus William; Graaf, Rick de; Erbel, Christian (Vasa, 2018)
. Postthrombotic syndrome (PTS) is the most common complication after iliofemoral deep vein thrombosis. It reduces quality of life and increases deep vein thrombosis (DVT)-related costs. The clinical symptoms and severity of PTS may vary; the most common symptoms include edema, pain (venous claudication), hyperpigmentation, lipodermatosclerosis, and ulceration. PTS is based on the principle of outflow obstruction, which may be caused by venous hypertension and may lead to valvular damage and venous reflux or insufficiency. Recent technical developments and new stent techniques now allow recanalisation of even complex venous outflow obstructions within the iliac vein and the inferior vena cava. This manuscript gives an overview on the latest standards for venous recanalisation.
Gesehen am 14.02.2020